2022
DOI: 10.1093/jcag/gwab042
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on IBD Care in Alberta: Patient and Provider Perspectives

Abstract: Objective The COVID-19 pandemic necessitated changes in the delivery of ambulatory care for patients with inflammatory bowel disease (IBD), including transitioning many visits to virtual formats and delaying non-urgent assessments. We aimed to evaluate the impact of the COVID-19 pandemic on IBD patient care from health care providers’ (HCP) and patients’ perspectives. Methods We administered a 42-question HCP survey and a 44-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Moreover, a previous study of MBSR in the general population demonstrated similar attrition when comparing in-person delivery of MBSR with digital delivery [ 35 ]. In view of all 3 studies being conducted in different geographical locations and at different times, it is possible that the study populations differ in their comfort levels with telehealth; however, a recent survey of IBD patients in Alberta found that over 80% of respondents were comfortable using virtual care options and agreed they were satisfied with telehealth as a treatment modality [ 36 ], and a previous study in the same geographical area with a similar IBD population found no challenges with attrition [ 37 ]. While attrition observed in our study could reflect random variation arising from the small number of participants, future studies should investigate if v-MBSR groups are noninferior to in-person MBSR groups with respect to completion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study of MBSR in the general population demonstrated similar attrition when comparing in-person delivery of MBSR with digital delivery [ 35 ]. In view of all 3 studies being conducted in different geographical locations and at different times, it is possible that the study populations differ in their comfort levels with telehealth; however, a recent survey of IBD patients in Alberta found that over 80% of respondents were comfortable using virtual care options and agreed they were satisfied with telehealth as a treatment modality [ 36 ], and a previous study in the same geographical area with a similar IBD population found no challenges with attrition [ 37 ]. While attrition observed in our study could reflect random variation arising from the small number of participants, future studies should investigate if v-MBSR groups are noninferior to in-person MBSR groups with respect to completion.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the selected articles in this review report difficulties in establishing trust and patient-provider relationships during video consultations. [17][18][19][20][21] The challenges reported in the literature can be grouped under two themes: (1) trust and physical distance, and (2) confidence in clinical assessment and embodied engagement.…”
Section: Patient-provider Communication Challengesmentioning
confidence: 99%
“…22,23 Trust in the technology, trust in the patient performing a physical exam, and trust in the physician providing the best care are some of the patient and provider reported concerns. Patients experience challenges related to the complexity of scheduling appointments, 17 technical difficulties such as time lags that can cause a degree of talking over and affect the consultation, 15 limited access to technology or a lack of technical skills, 21,24,25 and the system security and privacy. [24][25][26] In the context of video consultations, trust is difficult due to compromised nonverbal communication, 18 the lack of physical touch, and the general feeling of loss experienced on both sides of the screen.…”
Section: Trust and Physical Distancementioning
confidence: 99%
See 2 more Smart Citations